2001
DOI: 10.1038/sj.sc.3101229
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise testing with increasing inclination as exercise protocol for wheelchair athletes

Abstract: Study design: Treadmill testing on a progressive incline of 11 wheelchair athletes. Objective: To determine if a novel treadmill exercise protocol which uses increments in inclination, rather than the standard increments in velocity, can be used to e ectively determine maximum oxygen uptake VO 2max for elite wheelchair athletes. Setting: Nottwil, Switzerland. Methods: Eleven elite wheelchair basketball players (29.3+6.3 years, 72.7+16.9 kg and 177+9.6 cm) performed an exercise protocol with increasing inclinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
(16 reference statements)
0
14
0
1
Order By: Relevance
“…Persons with long-standing SCI generally have a higher VO 2peak than persons with a recent SCI. 12,73 Protocol differences could also explain the differences found; 20,23,43,74 overall, the ACE started at a higher power output, and had greater subsequent increments. It is suggested that greater increments may underestimate peak values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Persons with long-standing SCI generally have a higher VO 2peak than persons with a recent SCI. 12,73 Protocol differences could also explain the differences found; 20,23,43,74 overall, the ACE started at a higher power output, and had greater subsequent increments. It is suggested that greater increments may underestimate peak values.…”
Section: Discussionmentioning
confidence: 96%
“…The outcome of the maximal exercise tests were expressed as peak levels of oxygen uptake and power output (instead of maximal levels), because some subjects may have been able to activate a larger muscle mass, either through activation of the lower limbs (eg in those with incomplete lesion), or without the restraints from overuse and fatigue of the upper extremities. 21,34,75 The large variability in results found in paraplegia may be attributed to differences in measurement protocol 20,23,74 and study population. 3 Because of lack of homogeneity, no consistent conclusions on the influence of a particular protocol can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…For athletes, experts recommend performing exercise testing with activities as closely aligned to the sports activity as possible (Knechtle & Kopfli, 2001). Thus, walking/running on a treadmill was selected for exercise testing among adolescents as it simulates the PA that they engage in most frequently, can be assessed in a controlled environment, and does not require a high level of physical skill.…”
Section: Methodsmentioning
confidence: 99%
“…Também com paraplégicos Knechtle e Kopfli. 15 , analisaram 11 jogadores de basquete em cadeira de rodas (média de idade de 28 anos). Neste estudo, foi aplicado um protocolo de exercício físico com aumento da inclinação na esteira para verificação da possibilidade de utilização de um protocolo com inclinação na esteira em pessoas com lesão da medula espinhal (abaixo de T1).…”
Section: Resultsunclassified